Dapatkah Earnings Quality Memoderasi Pengaruh Faktor Keuangan dan Non Keuangan terhadap Dividend Trend? - Mekani Vestari; Muhammad Yusuf (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to obtain empirical evidence that earnings quality strengthens / weakens the effect of profitability trend, leverage trend, liquidity trend, firm size trend, on dividend trend. The analysis method used is MRA (Multiple Regression Analysis). The analysis method used is MRA (Multiple Regression Analysis). The research object is all non-financial companies listed on the Indonesia Stock Exchange (BEI) in the 2014 to 2014 research period. 2018. The results show that earnings quality is able to strengthen the effect of the profitability trend, liquidity trend, and firm size trend on the dividend trend. This study is also able to prove that earnings quality is able to weaken the influence of the leverage trend on the dividend trend. Overall, the results of the study indicate that earnings quality is a purely moderating variable for the effect of profitability trend, leverage trend, liquidity trend, firm size trend on dividend trend